Characterization of HAK protein family in Casuarina equisetifolia and the positive regulatory role of CeqHAK6 and CeqHAK11 genes in response to salt tolerance - Wang, Yujiao; Zhang, Yong; Wei, Yongcheng; Meng, Jingxiang; Zhong, Chonglu; Fan, Chunjie (Frontiers in Plant Science, 2023)
The potassium transporter group of the HAK/KUP/KT (high-affinity K+)/KUP (K+ uptake)/KT (K+ transporter) family plays a crucial role in plant growth and development as well as in environmental adaptation such as tolerance to salt stress. HAK/KUP/KT genes and their functions have been characterized for a number of plant species, but they remain unknown for Casuarina equisetifolia, an important tree species for coastal protection in southern China and many other countries. In this study, 25 HAK genes were identified in the C. equisetifolia genome. Their gene structure, conserved motif, phylogeny, and expression were comprehensively and systematically analyzed to understand their functions. All HAK genes were relatively conserved and could be divided into four clusters. The expression level of two particular genes, CeqHAK11 and CeqHAK6, increased significantly with the duration of salt treatment. To further elucidated their function in response to salt stress, subcellular localization, and their functional analysis were developed. Results revealed that CeqHAK11 and CeqHAK6 were localized on the plasma membrane, which mainly mediated high-affinity K+ uptake. Overexpression of CeqHAK6 or CeqHAK11 in Arabidopsis showed higher germination and survival rates and longer root length than wild-type (WT) under salt stress, suggesting that both genes improve tolerance to salt stress. Moreover, CeqHAK6 and CeqHAK11 improved their ability to tolerate salt stress by increasing the K+/Na+ ratio and antioxidant enzyme activities (CAT, POD, and SOD), and decreasing reactive oxygen species (ROS) accumulation. Consequently, CeqHAK6 and CeqHAK11 were verified as potassium transport proteins and could be applied for further molecular breeding for salt tolerance in C. equisetifolia or other crops to increasing salt tolerance.